PENGARUH REALIMENTASI TERHADAP PERKEMBANGAN BERAT BADAN DAN MORFOLOGI USUS HALUS PADA TIKUS MALNUTRISI - Endi Ridwan; Rustadi Sosrosumihardjo (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2005)
ABSTRACT Introduction: Intra Uterine Growth Retardation (IUGR) cause the weight of baby body born to lower, as a result can cause the malnutrition. The most common etiology of failure to thrive in infants due to gastrointestinal origin, particularly nutrient maldigestion , malabsorbtion and chronic diarrhea. Malnutrition can be overcome with the gift of square meal and well-balanced by energy required to pursue the growth. Objectives: Learning growth response of body weight, morphology of intestinal parameters and activities of disaccharidases enzyme. by using rats as animal model. Methods: This Research is experimental. Malnutrition rats were made with the restriction  diet of equal to 50 percent  since gestation period, lactation and 3 week after delivering birth. Realimentation were conducted during 8 week, with the food gift ad libitum and use the control. Parameters  perceived is ; body weight, morphology and morphometry of small intestine, serum of albumin and enzyme activities in disaccharidase. Results: The body weight of rats in realimentation group was higher than malnutrition group, but lower than control group.  The morphology and morfometri of small intestine showed  the increase have a meaning , and so do serum of albumin and activities of  disaccharidases enzym. Conclusions: Realimentation at malnutrition rats can improve the body weight, morfology and morphometry of small intestine, and also enzyme activities in disaccharidases. [Penel Gizi Makan 2005,28(2): 72-78] Keywords: malnutrition rats, realimentation, small intestine, body weight